Rare Metal Technology 2017 - Kim, Hojong; Alam, Shafiq; Neelameggham, Neale R.; Oosterhof, Harald; Ouchi, Takanari; Guan, Xiaofei (Springer International Publishing : Imprint: Springer, 2017)
This collection presents papers from a symposium on extraction of rare metals as well as rare extraction processing techniques used in metal production. Topics include the extraction and processing of elements like antimony, arsenic, gold, indium, palladium, platinum, rare earth metals including yttrium and neodymium, titanium, tungsten, and vanadium. Rare processing techniques are covered, including direct extraction processes for rare-earth recovery, biosorption of precious metals, fluorination behavior of uranium and zirconium mixture of fuel debris treatment, and recovery of valuable components of commodity metals such as zinc, nickel, and metals from slag.
Keywords: Materials science.; Structural materials.; Metals.; elektronické knihy; electronic books